Air pollution and family related determinants of asthma onset and persistent wheezing in children: nationwide case-control study. (19th August 2020) - Holst, Gitte J; Pedersen, Carsten B; Thygesen, Malene; Brandt, Jørgen; Geels, Camilla; Bønløkke, Jakob H; Sigsgaard, Torben
Abstract: Objective: To identify risk factors (air pollution and family related) for the onset of asthma and persistent wheezing in children. Design: Nationwide case-control study. Setting: Denmark. Participants: All Danish children born from 1997 to 2014 and followed for asthma onset and persistent wheezing from age 1 year to 15 years. Main outcome measure: Onset of asthma and persistent wheezing. Results: A higher incidence of asthma was found in children of parents with asthma (adjusted hazard ratio 2.29 (95% confidence interval 2.22 to 2.35) and mothers who smoked during pregnancy (1.20, 1.18 to 1.22), whereas a lower incidence was found in children of parents with high educational attainment (0.72, 0.69 to 0.75) and high incomes (0.85, 0.81 to 0.89). Exposure to particulate matter ≤2.5 µm (PM2.5 ) and ≤10 µm (PM10 ) and nitrate was associated with an increased risk of asthma and persistent wheezing, with hazard ratios per 5 µg/m 3 increase in pollutant concentrations 1.05 (1.03 to 1.07) for PM2.5, 1.04 (1.02 to 1.06) for PM10, and 1.04 (1.03 to 1.04) for nitrogen dioxide. Only the positive association of PM2.5 with asthma and persistent wheezing remained robust across the different models and in sensitivity analyses. Conclusions: The findings of this study suggest that children exposed to higher levels of PM2.5 are more likely to develop asthma and persistent wheezing than children who are not exposed. Other risk factors associated with these outcomes were parental asthma, parental education, and maternal smoking during pregnancy.